Interpersonal Violence Around Pregnancy Experienced by Rural and Urban Canadian Women: Correlates and Selected Health Outcomes - Su, Yingying; D’Arcy, Carl (Journal of interpersonal violence, 2022)
Interpersonal violence around pregnancy is of increasing global public health concern affecting both women themselves and their children. The primary aim of this study is to explore and identify potential correlates of such violence and to examine maternal and birth outcomes subsequent to that violence in a nationally representative sample of urban and rural women in Canada. The data are from the Maternity Experiences Survey (MES), a Canadian population-based postcensus survey administered to 6,421 Canadian mothers in 2006. Survey participants were 15 years and older and had given birth to a singleton and continued to live with their infant at the time of the survey. The survey response rate was 78%. Multivariable logistic regression analyses were used in the analysis with adjustments made for confounding variables. The study findings indicated that living in an urban environment was associated with an increased risk of interpersonal violence experience around the time of pregnancy (OR = 1.31, 95% CI: 1.03-1.66). In addition, being aboriginal, young, unmarried, economically disadvantaged, a nonimmigrant, and having more than four pregnancies, as well as cigarette smoking, alcohol drinking and drug use before the pregnancy were correlated with interpersonal violence around pregnancy. Maternal interpersonal violence experiences were also associated with postnatal depression and stressful life events among both urban and rural mothers. However, maternal interpersonal violence experiences were only associated with preterm birth among rural mothers but not among urban mothers. The present study highlights the need to implement effective interventions for women experiencing interpersonal violence around pregnancy due to its potential impact on maternal and newborn’s physical and mental health. Screening and intervention should be targeted high-risk women particularly those who are indigenous, young, unmarried, nonimmigrants, of lower socioeconomic status, and manifesting high risk health behaviors.